Analisis Pemetaan Jaringan Komunikasi Karyawan Menggunakan Social Network Analysis pada Perusahaan Multifinance - Zusrony, Edwin; Purnomo, Hindriyanto Dwi; Prasetyo, Sri Yulianto Joko (INTENSIF: Jurnal Ilmiah Penelitian dan Penerapan Teknologi Sistem Informasi, 2019)
Business development in the financial services sector improved competition among companies to give the best service to their customers. Having reliable services with a good communication network in the organization is the critical success of the company. This study aims to find the actors or people who influence organizations through formal and informal communication networks using Social Network Analysis (SNA). Information on casual and formal communication networks can be used by the HR department to measure the level of the social relationship of all employees that can improve their performance in the company. The author researched PT. BFI Salatiga. The results showed that tissue density was below 50% so that relationships were considered weak. The most dominant actor in degree centrality, closeness centrality, and betweenness centrality is the actor id#24 and id#29 from the collection division, actor id#27 from the operation division and actor id#30 from the credit division.